Equilibrium in adversity: balancing public service supply and demand during population decline - Xiaomei Li; Jing Zhu; Jiangjun Wan; Ziming Wang (Humanities & Social Sciences Communications)
Abstract Amidst global demographic shifts, China’s negative population growth since 2022 underscores the urgent need for population-adaptive public service equilibrium. This study assesses the coupling coordination degrees between population and public service (P-PS CCD) across 1733 Chinese counties for the years 2000, 2010, and 2020, employing the Geographical Detector Model (GDM) to examine influencing factors. The findings reveal consistently low P-PS CCD levels, indicating a delayed response of public service systems to population trends and significant spatial disparities influenced substantially by administrative factors. This research offers valuable insights for countries and regions experiencing or about to experience similar population changes.